THE REPRESNTATION OF SUBALTERN IN CHRISTINA LAMB AND MALALA YOUSAFZAI'S MEMOIR "I AM MALALA" - Siti Hardiyanti Amri (TELAGA BAHASA, 2018)
AbstractThe portrait of the condition of the marginal occasionally becomes the theme in the works of some authors, including Malala Yousafzai. This research is an attempt to find out the representation of subaltern as the central issue in Christina lamb and Malala Yousafzai's memoir I Am Malala using Gayatri Spivak subalternity theory. Spivak explained that subaltern refers to people from inferior position or class. The method of deconstruction is conducted to identify hidden texts behind all the hierarchical oppositions in the series of events presented by the author through his work. The dominant structure in memoir is demonstrated through the hierarchical relation between men and women, the Taliban and civil society, as well as government and civil society. Nevertheless, through his memoir, Malala represented that subaltern are also able to voice themselves for their rights to justice, peace, especially education for women. The research eventually revealed that Malala and his father are not in subaltern position but in the position to be heard because of the space that allowed them both to voice or articulate themselves.